Explaining disaster: tradition and transformation of the "Catastrophe of Ibbi-Sîn" in Babylonian Literature - Schaudig, Hanspeter (Zaphon Verlag, 2019)
Intro -- Table of Contents -- Preface -- 1. Introduction -- 1.1. The Subject -- 1.2. History of Research -- 1.3. Method -- 1.4. Selecting the Sources -- 1.5. Range of Topics -- 1.6. Intentional History and Typification -- 1.7. Excursus: "Nebuchadnezzar", Khosrau and Jerusalem -- 2. Ibbi-Sîn King of Ur -- 2.1. General Outlines of Ibbi-Sîn's Reign -- 2.2. Ibbi-Sîn's Family Relations -- 2.3. Ibbi-Sîn's Name and Titles -- 2.4. Ibbi-Sîn's End -- 3. The Figure of Išbi-Erra and Isin as Heiress of Ur -- 4. Destructions of Babylon and Abductions of Marduk -- 4.1. Divine Primacy of Agency -- 4.2. The Abductions of Marduk -- 4.3. Ancient Explanations -- 5. The Formation of a Tradition -- 5.1. Isin's Answer -- 5.2. Larsa's Answer -- 6. The Tradition of the Historical Omens -- 6.1. The Ibbi-Sîn Omens -- 6.2. Excursus: The Element "Four" and the "Four Winds of Heaven" -- 6.3. Excursus: The "Oracle of the Square Temple" at Jerusalem -- 7. The Formation of a Rationale: The Esaĝil Chronicle -- 7.1. Sin and Sanction: Mirror Punishment -- 7.2. Sin and Sanction: Collective Punishment -- 7.3. Historical Part -- 7.4. The Abuse of the Fish Offering to Marduk -- 8. More Disaster: The Religious Chronicle &amp -- The Book of Prodigies -- 8.1. The Tower of Babel: When Adad smote Etemenanki -- 8.2. The Tower of Babel: Jewish-Babylonian Traditions -- 9. Periodicity of Disasters? -- 10. The Impact of the Compositions on Politics -- 10.1. Sargon II and Marduk-apla-iddina II: The New Ibbi-Sîn? -- 10.2. Aššurbanipal and Bēl-ēṭir: The New Utu-ḫeĝal? -- 10.3. Nebuchadnezzar II and the Fish Offering to Marduk -- 10.4. The Sins of Nabonidus -- 10.5. Dareios and the Fall of Babylon -- 10.6. Xerxes and the Statue of Marduk -- 11. The Participants -- 11.1. The Gods -- 11.2. Kings and Priests -- 11.3. The People -- A. ṣābū kidinni "The Privileged Citizens (of a Babylonian City)
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift; Sintflut; Literatur; Babylonisch; Sumerisch